Zoom surprising ways to supercharge your career - Roberts, Daniel (New York Fortune Books, an imprint of Time Home Entertainment Inc., 2013)
Foreword / Marc Andressen -- Introduction / Leigh Gallagher -- 1. Challenge Goliath / Kevin Plank, Katrina Markoff, John Janick -- 2. Get in over your head / Marissa Mayer, Elon Musk, Meredith Whitney -- 3. Start a cult / Tony Hsieh, Larry Page, Sergey Brin, Eric Ryan, Adam Lowry -- 4. Follow your first love / David Chang, Kevin Fiege, Seth Macfarlane -- 5. Find a problem / Jennifer Hyman, Jennifer Fleiss, Perry Chen, Yancey Strickler, Charles Adler, Brian Chesky -- 6. Do one thing well / Jess Lee, Kevin Systrom, Biz Stone, Ev Williams -- 7. Stand by your company / Dolf van den Brink, Rob Goldstein , Aditya Mittal -- 8. Think of others / Scott Harrison, Ben Rattray, Blake Mycoskie -- 9. Bounce back / Hosain Rahman, Boaz Weinstein, Lebron James -- In their own words: tips and advice from zoomers -- Appendix: Where are they now? The 40 under 40 class lists.
Offers the secrets to success from the top business leaders and entrepreneurs as featured in Fortune magazine's 40 Under 40 series, including wisdom and advice from Mark Zuckerburg, Jack Dorsey, and Ryan Seacrest.
Keywords: Success in business